1993
DOI: 10.1007/bf00146291
|View full text |Cite
|
Sign up to set email alerts
|

Study of environmental isotope distribution in the Aswan High Dam Lake (Egypt) for estimation of evaporation of lake water and its recharge to adjacent groundwater

Abstract: Oxygen-18 ((18)0) and deuterium isotopes were used to estimate the evaporation from the Aswan High Dam Lake and to investigate the inter-relation between the lake water and adjacent groundwater.According to stable isotopic analysis of samples taken in 1988 and 1989, the lake can be divided into two sections. In the first section extending between Abu Simbel and a point between EI-Alaki and Krosko, a remarkable vertical gradient of (18)0 and deuterium isotopic composition was observed. The second northern secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…The Palaeozoic and Mesozoic successions form productive aquifers and contain fossil ground water that was recharged during wet palaeoclimatic periods (Aly et al, 1993;RIGWA, 1998). The regional ground water flow is from southwest to northeast (Ball, 1927).…”
Section: Ground Watermentioning
confidence: 99%
“…The Palaeozoic and Mesozoic successions form productive aquifers and contain fossil ground water that was recharged during wet palaeoclimatic periods (Aly et al, 1993;RIGWA, 1998). The regional ground water flow is from southwest to northeast (Ball, 1927).…”
Section: Ground Watermentioning
confidence: 99%
“…Areas to the west of the Nakhlai‐Aswan uplift (see cross section 2 in Figure ) are principally composed of low‐productive aquifers with paleokarst features, whereas areas to the east of the uplift are largely composed of highly to moderately productive aquifers, formed of coarse‐ to medium‐grained Paleozoic and Mesozoic sandstone with minor intercalations of shales (RIGW, ; Kim and Sultan, ). Both kinds of aquifers contain fossil groundwater recharged during wet paleoclimatic periods (Aly et al ., ; RIGW, ; Kim and Sultan, ). However, areas east of the uplift could have been recharged more recently (Abdel Karim, ).…”
Section: Hydrogeological Description Of the Study Areamentioning
confidence: 98%
“…contain fossil groundwater recharged during wet paleoclimatic periods (Aly et al, 1993;RIGW, 1998a;Kim and Sultan, 2002). However, areas east of the uplift could have been recharged more recently (Abdel Karim, 1992).…”
Section: Hydrogeological Description Of the Study Areamentioning
confidence: 99%
“…In Africa, Aly et al . () observed that evaporation from the Aswan High Dam removed approximately 19% of the input water flow. In North America, Gat et al .…”
Section: Introductionmentioning
confidence: 99%
“…These researchers observed that a 1% loss of River Murray water under summer conditions by evaporation resulted in a mean increase in the value of δD of approximately 0·6-1·0% in the surface water. In Africa, Aly et al (1993) observed that evaporation from the Aswan High Dam removed approximately 19% of the input water flow. In North America, Gat et al (1994) estimated the evaporation from the Great Lakes on the basis of the isotope method and observed that between 4·6% and 15·7% of the atmospheric water content came from lake evaporation during summer.…”
Section: Introductionmentioning
confidence: 99%